Computing permissible design spaces under consideration of functional responses. (March 2018) - Graf, W.; Götz, M.; Kaliske, M.
Highlights: Combination of different soft computing to solve the inverse problem. Approach is based on existing point sets and could consider functional responses. Efficient interval approach to compute the best permissible design space. Abstract: The design of structures is one of the major tasks for engineers. The objectives of numerical design – computing robust and reliable structures – can be realized by means of analyzing different variants, application of optimization tasks, or solving inverse problems. The method of choice depends on the objective of design, the problem and available data/resources. This contribution introduces an application oriented procedure for the solution of an inverse problem, on the basis of existing data. This data consists of design vectors and related responses. This contribution is focused on functional responses. With this procedure independent areas of permissible designs can identified. These areas are approximatively described by hyperrectangles, which are multi-dimensional boxes. The procedure uses various algorithms within the context of data mining. The relevant methods will be discussed shortly. The proposed field of application is the detection permissible design spaces in early design stages. Therefore the applicability of the presented procedure is shown by practical numerical design studies.